Resource allocation in NOMA heterogeneous network based on MEC - Haijun ZHANG; Zizheng ZHANG; Keping LONG (Tongxin xuebao)
Aiming at maximizing the cache revenue,a joint user association and power allocation algorithm was proposed for the matching of base stations with users and power allocation in a NOMA heterogeneous network with caches,a NOMA joint optimization algorithm which was achieved by combing with message passing and DC programming was proposed.First,the constraints were incorporated into the objective function,and the user association result was obtained by calculating the marginal of the message passing between the function node and the variable node in the new optimization problem.Then,the original optimization problem was transformed into the form of the difference between two convex functions,and allocate power resources through DC programming.Finally,the final user association and power allocation results are obtained through iterative calculations.Simulation results prove that the proposed algorithm effectively improves network performance.